2005
DOI: 10.1080/02786820500182404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Stick on the Gas Turbulence Structure in a Cyclone Separator

Abstract: Laser Doppler Velocimetry (LDV) was used to measure the turbulence structure of the flow field in a cyclone separator. The measurement results showed that a stick inserted in the cyclone changed the distribution of the flow field. A flow wake region downstream the stick decreased the tangential velocity and increased the turbulence intensity. The size and shape of the stick cross-section had a remarkable effect on the distribution of the flow wake and the turbulence structure of the flow field. The changes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…However, at inlet velocity of 16.72 m s -1 and fibrous filter width of 4 mm, the penetration is higher than that of the cyclone for the particle size of 1.0 μm. This is because the cyclone flow field was disturbed by the filters, similar to the results of Wang et al (2005). They reported that the insertion of the stick into the cyclone changed the cyclonic flow distribution by decreasing the tangential velocity and increasing the turbulence intensity.…”
Section: Effect Of Particle Size For the Combined Cyclone-fibrous Filsupporting
confidence: 74%
See 2 more Smart Citations
“…However, at inlet velocity of 16.72 m s -1 and fibrous filter width of 4 mm, the penetration is higher than that of the cyclone for the particle size of 1.0 μm. This is because the cyclone flow field was disturbed by the filters, similar to the results of Wang et al (2005). They reported that the insertion of the stick into the cyclone changed the cyclonic flow distribution by decreasing the tangential velocity and increasing the turbulence intensity.…”
Section: Effect Of Particle Size For the Combined Cyclone-fibrous Filsupporting
confidence: 74%
“…4.7 shows that the pressure drop of combined cyclone-filter collectors is smaller than that of cyclone. This is due to the presence of the filter causes the increasing of the turbulence intensity affecting in the reduction of tangential velocity (Wang et al 2005). For the cyclone combined with fibrous filter 4-mm and 8-mm-width, the pressure drop is lower by 32.7 and 38.8%, respectively.…”
Section: Pressure Drop Of the Combined Cyclone-filter Collectormentioning
confidence: 89%
See 1 more Smart Citation
“…Hoffman et al [22] and Safikhani et al [23] concentrated on study of the height of the cyclones. Furthermore, the effect of holes in the cyclone and hem of the internal walls of the cyclone was studied by Wang et al [24] and Farahani et al [25] respectively. Su and Mao [26], Safikhani et al [27] and Su et al [28] investigated the performance of the rectangular cyclone.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have been conducted with laser Doppler velocimetry (LDV) techniques to measure the mean and fluctuating velocity components inside a cyclone. Wang et al (2005) measured the turbulent structure of flow field and analyzed a flow wake region downstream of a stick inserted into a cyclone. Erdal and Shirazi (2004) conducted measurements at 24 axial locations in a cylindrical cyclone to understand the swirling flow behavior.…”
Section: Introductionmentioning
confidence: 99%